Art, Ideology, and Language: A Critical Discourse Analysis of Cultural Representation in Anwar Beck's Songs - Irawan Sukma; Sri Rochana Widyastutieningrum; Aton Rustandi Mulyana (Yayasan Keluarga Guru Mandiri, 2025)
In the context of Anwar Beck, his lyrics reflect a sensitivity to cultural, social, and local identity issues in Palembang. However, in-depth studies on the influence of personal and social ideology in his works remain scarce. This study examines the ideology underlying the creative process of musician Anwar Beck and how this ideology is represented in the lyrics and themes of his songs. Using a qualitative approach and critical discourse analysis, this research explores Beck's ideological views through in-depth interviews, an analysis of the lyrics of five selected songs: Musimu Musiku, Raso-raso, Keladi Tumbuh di Lebak, Kemano Pegi, and Kembang Sriwijaya, as well as a literature review on the theory of ideology in art and music. The data analysis techniques used include thematic analysis to identify ideological patterns in the song lyrics and interviews, along with data validation through source and method triangulation. The study results show that Anwar Beck's songs embody a complex ideology, blending criticism of local culture's marginalization with efforts to preserve and empower Palembang's cultural identity. Bahasa Palembang Halus and Sari-sari serve as mediums for Beck's artistic ideology and strategies for preserving Palembang's cultural and linguistic values.